Baseline surgical status and short-term mortality after extracorporeal membrane oxygenation for post-cardiotomy shock: a meta-analysis. (April 2020) - Kowalewski, Mariusz; Raffa, Giuseppe; Zieliński, Kamil; Meani, Paolo; Alanazi, Musab; Gilbers, Martijn; Heuts, Samuel; Natour, Ehsan; Bidar, Elham; Schreurs, Rick; Delnoij, Thijs; Driessen, Rob; et al.
Objective: While reported mortality rates on post-cardiotomy extracorporeal membrane oxygenation vary from center to center, impact of baseline surgical status (elective/urgent/emergency/salvage) on mortality is still unknown. Methods: A systematic search was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement using PubMed/Medline databases until March 2018 using the keywords "postcardiotomy, " "cardiogenic shock, " "extracorporeal membrane oxygenation, " and "extracorporeal life support." Relevant articles were scrutinized and included in the meta-analysis only if reporting in-hospital/30-day mortality and baseline surgical status. The correlations between mortality and percentage of elective/urgent/emergency cases were investigated. Inference analysis of baseline status and extracorporeal membrane oxygenation complications was conducted as well. Results: Twenty-two studies (conducted between 1993 and 2017) enrolling N = 2, 235 post-cardiotomy extracorporeal membrane oxygenation patients were found. Patients were mostly of non-emergency status (65.2%). Overall in-hospital/30-day mortality event rate (95% confidence intervals) was 66.7% (63.3-69.9%). There were no differences in in-hospital/30-day mortality with respect to baseline surgical status in the subgroup analysis (test for subgroup differences; p = 0.406). Similarly, no differences between mortality in studies enrolling <50 versus ⩾50% of emergency/salvage cases was found: respective event rates were 66.9% (63.1-70.4%) versus 64.4% (57.3-70.8%); p = 0.525. Yet, there was a significant positive association between increasing percentage of emergency/salvage cases and rates of neurological complications (p < 0.001), limb complications (p < 0.001), and bleeding (p = 0.051). Incidence of brain death (p = 0.099) and sepsis (p = 0.134) was increased as well. Conclusion: Other factors than baseline surgical status may, to a higher degree, influence the mortality in patients treated with extracorporeal membrane oxygenation for post-cardiotomy cardiogenic shock. Baseline status, however, strongly influences the complication occurrence while on extracorporeal membrane oxygenation.